Conservation and efficient utilization of resources: a major indicator of China's economic transformation - Zhang Zhuoyuan (China Finance and Economic Review, 2015)
After more than 30 years of rapid growth, China's economy is increasingly faced with the bottleneck brought about by resources and environment. To achieve a sustained economic growth, more attention should be paid to the safety of the arable land, fresh water, energy, and other important resources. Great efforts should be made to transform the mode of economic development, adjust the economic structure, deepen reform, and expand opening-up. It is necessary to promote the transformation of the growth means characterized by ineffective utilization of resources and extensive expansion to the one characterized by intensive and efficient utilization of resources as well as quality and efficiency so that the economy and society are really going toward the track of scientific development.
Keywords: 330; Resource conservation; Efficient use of resources; Economic restructuring